The Effect of Baby Swimming on Gross Motor Development in Babies Aged 3-9 Months - Siti Nur Fadilah Sujak; Anik Purwati (Health and Technology Journal (HTechJ), 2026)
Infancy represents a critical period for growth and neurodevelopment, during which appropriate stimulation is essential to optimize developmental outcomes. Baby swimming has been proposed as an early stimulation intervention that may promote motor development through structured movement in a warm-water environment. This study aimed to examine the effect of baby swimming on gross motor development in infants aged 3–9 months. A quantitative study was conducted using a pre-experimental one-group pretest–posttest design. The sample consisted of 15 infants aged 3–9 months recruited from Yuki Mom and Baby Spa, Probolinggo City, Indonesia, using purposive sampling. The intervention involved baby swimming sessions in a warm pool (38–40°C) using a baby float for 10–15 minutes. Gross motor development was assessed before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test. The results showed a statistically significant improvement in gross motor development following the intervention (p = 0.02). These findings suggest that baby swimming may have a positive effect on gross motor development in early infancy. Baby swimming can be considered a potential non-pharmacological intervention to support gross motor development in infants. However, further studies with larger sample sizes and controlled designs are recommended to strengthen the evidence.